The Influence of Financial Factors on Tax Avoidance Practices, Moderated by the Role of Women on the Board of Directors: Case Study of a Mining Company Registered on the IDX from 2018 to 2022 - Mulasimadhi, Yoza; Nusanto, Galih Wibowo; Reskino, Reskino (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to investigate the impact of financial factors on the fulfillment of corporate tax obligations, especially in the mining sector, from 2018 to 2022. In addition, this research explores the role of women in top management and how their presence can influence tax avoidance practices. The research results show that financial factors have a significant impact on corporate tax avoidance practices. When moderated by the presence of women in top management, the impact of these factors can weaken tax avoidance practices. This research contributes to the understanding of the relationship between financial factors and tax avoidance, especially in the context of the mining sector by involving women in top management. However, this study recognizes shortcomings, such as the limited sample size and the proportion of variation influenced by other independent variables. Therefore, further research is recommended to improve this weakness by adding variables or expanding sector coverage.